Landscape Management for Sustainable Supplies of Bioenergy Feedstock and Enhanced Soil Quality - Karlen, Douglas L.; Muth, David J. Jr. (Agrociencia Uruguay, 2013)
Agriculture can simultaneously address global food, feed, fiber, and energy challenges provided our soil, water, and air resources are not compromised in doing so. Our objective is to present a landscape management concept as an approach for integrating multiple bioenergy feedstock sources into current crop production systems. This is done to show how multiple, increasing global challenges can be met in a sustainable manner. We discuss how collaborative research among USDAAgricultural Research Service (ARS), US Department of Energy (DOE) Idaho National Laboratory (INL), several university extension and research partners, and industry representatives [known as the Renewable Energy Assessment Project (REAP) team] has led to the development of computer-based decision aids for guiding sustainable bioenergy feedstock production. The decision aids, known initially as the «Corn Stover Tool» and more recently as the «Landscape Environmental Assessment Framework» (LEAF) are tools designed to recognize the importance of nature’s diversity and can therefore be used to guide sustainable feedstock production without having negative impacts on critical ecosystem services. Using a 57 ha farm site in central Iowa, USA, we show how producer decisions regarding corn (Zea mays L.) stover harvest within the US Corn Belt can be made in a more sustainable manner. This example also supports REAP team conclusions that stover should not be harvested if average grain yields are less than 11 Mg ha-1 unless more balanced landscape management practices are implemented. The tools also illustrate the importance of sub-field management and site-specific stover harvest strategies.